Visceral pathology of hereditary tyrosinemia type I. - Russo, P (1990)
The major pathological findings in 23 patients with hereditary tyrosinemia type I seen at the Hôpital Sainte-Justine over a 23-year period are reviewed in combination with findings in the literature. Hepatic and renal alterations are given special emphasis. Hepatic changes differ in the acute and chronic forms of the disease. The former is characterized by alterations shared by several hepatopathies of infancy, whereas the latter is characterized by established cirrhosis, frequently of a mixed macro- and micronodular type, with a frightening propensity for the development of hepatocellular carcinoma. Renal changes reflect tubular injury, resulting in Fanconi syndrome, with tubular dilatation, nephrocalcinosis, and involution of epithelial cells. A significant proportion of patients also reveal some degree of glomerulosclerosis and interstitial fibrosis, indicating at least the need for careful assessment and follow-up of renal function, particularly in light of the adverse renal effects of immunosuppressive regimens used in liver transplantation.